Environmental Factors in Tropical Diseases in Rural Children: A Systematic Review - Budiman (Yayasan Sinergi Kawula Muda, 2022)
Tropical diseases remain a significant public health burden among children in rural areas, where environmental factors, limited healthcare access, and socioeconomic disparities contribute to high morbidity and mortality rates. This study evaluates the impact of climatic variables, inadequate water, sanitation, and hygiene (WASH) infrastructure, and healthcare accessibility on disease transmission. A systematic review of literature was conducted using multiple databases, including PubMed, Scopus, and Web of Science, employing keywords related to tropical diseases, environmental risk factors, and pediatric health. The results indicate that climate fluctuations significantly influence the incidence of vector-borne diseases such as malaria and dengue. Poor sanitation infrastructure is strongly associated with increased cases of diarrheal diseases and helminth infections. Additionally, rural communities face healthcare access limitations, resulting in delayed diagnoses and suboptimal treatment for affected children. Socioeconomic conditions further exacerbate these health disparities, leading to higher infection rates and adverse outcomes. indings suggest the need for integrated public health interventions that address environmental, healthcare, and socioeconomic determinants. Strengthening WASH infrastructure, improving healthcare accessibility, and implementing climate-responsive disease control strategies are essential for reducing the burden of tropical diseases in rural children. Future research should explore long-term intervention effectiveness and interdisciplinary approaches to mitigate disease transmission. Addressing these challenges through sustainable policy initiatives and community engagement is crucial for improving pediatric health outcomes in endemic regions.